Perilaku Pengelolaan Keuangan Generasi Z Ditinjau dari Literasi Keuangan, Kecerdasan Spiritual, dan Hedonisme Lifestyle - Muhammad Qoes Atieq; Devi Febriana Pratiwi (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2023)
Financial management is quite an important activity, especially for Generation Z as the next generation who can influence the country's economy. Poor financial behavior will reduce a person's standard of living. The aim of the research is to determine the level of financial literacy, spiritual intelligence and lifestyle hedonism on the financial management behavior of Generation Z in Pati Regency. This research used purposive sampling with a sample of 400 respondents. The analysis technique for this research uses the SPSS version 25 application, and data is obtained from distributing questionnaires online via form and distributing them directly to respondents. The results of this research show that financial literacy and spiritual intelligence have a positive influence on financial management behavior. Meanwhile, lifestyle hedonism has a negative influence on the financial management behavior of generation Z. The advice given is that generation Z needs to pay attention to their lifestyle so as not to be influenced by the negative impact of lifestyle hedonism, as well as increasing the level of literacy and spiritual understanding in order to create good financial management behavior.